2021
DOI: 10.3389/fmicb.2021.730809
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Short-Chain Fatty Acids of Gut Microbiota Origin in Hypertension

Abstract: Hypertension is a significant risk factor for cardiovascular and cerebrovascular diseases, and its development involves multiple mechanisms. Gut microbiota has been reported to be closely linked to hypertension. Short-chain fatty acids (SCFAs)—the metabolites of gut microbiota—participate in hypertension development through various pathways, including specific receptors, immune system, autonomic nervous system, metabolic regulation and gene transcription. This article reviews the possible mechanisms of SCFAs i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 161 publications
2
38
0
3
Order By: Relevance
“…Propionic acid is the primary metabolite of Bacteroidetes fermentation, inhibiting cholesterol synthesis (16). Based on previous studies, the clinical effects of propionic acid on lipid metabolism are manifested through lowering cholesterol concentrations and reducing fat storage (26). The present study found that propionic acid levels were significantly increased in PE patients.…”
Section: Discussionsupporting
confidence: 55%
“…Propionic acid is the primary metabolite of Bacteroidetes fermentation, inhibiting cholesterol synthesis (16). Based on previous studies, the clinical effects of propionic acid on lipid metabolism are manifested through lowering cholesterol concentrations and reducing fat storage (26). The present study found that propionic acid levels were significantly increased in PE patients.…”
Section: Discussionsupporting
confidence: 55%
“…Short-chain fatty acids not only affect immune cells, but also act as a source of energy, a participant in cells metabolism, a signal molecule recognized by specific receptors, and a regulator of gene expression, thereby having a significant impact on blood pressure regulation. 53,72,73 Both high-fibre diet and acetate supplementation regulated cardiac molecular pathways, decreased cardiac hypertrophy and fibrosis, lowered blood pressure and improved heart function in experimental hypertension. 74 Similarly, propionate treatment orally resulted in reduction in systolic and diastolic blood pressure along with reduced systemic inflammation in angiotensin-II induced hypertensive mice.…”
Section: Scfasmentioning
confidence: 99%
“…Several underlying mechanisms have been proposed to explain these effects, including specific receptors, autonomic nervous system, immune system, metabolic regulation and gene transcription. 65,73,76 Through binding receptors, such as GPR41, GPR43, GPR109A and olfactory receptor 78, SCFAs can directly regulate blood pressure. 53,77,78 Onyszkiewicz et al reported that butyrate can cross through the gut-vascular barrier into the bloodstream and operate on GPR41/GPR43 to relax the mesenteric artery, considerably reducing hypertension.…”
Section: Scfasmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, the microbiome releases by-products and secondary metabolites from dietary components that can serve as an excellent indicator for assessing diet-induced metabolic changes. Among these metabolites is the group of short-chain fatty acids (SCFAs) from which acetic, propionic and butyric acid make up 95% of the SCFAs produced in the gut (Wu et al, 2021). Production of SCFAs is a result of fermentation of (partially) non-digestible polysaccharides (NDP) (Forkman, 2009) in the colon, mainly emanating from highly resistant starches (Cummings et al, 1986).…”
Section: Introductionmentioning
confidence: 99%